Ijma’ sebagai landasan hukum dalam hukum negara - viona, amanah giovani visi yuti (Maliki Interdisciplinary Journal, 2025)
Ijma’ is one of the sources of Islamic law that holds a strategic position after the Qur’an and Sunnah. Historically, ijma’ is understood as the unanimous agreement of Islamic scholars at a certain time regarding a legal ruling that is not explicitly found in the text. In classical tradition, ijma’ functions as a collective mechanism that ensuring the stability, legitimacy, and continuity of Islamic law. With the advancement of time and the emergence of modern nation-states with pluralistic and democratic legal systems, the position and implementation of ijma’ face new challenges. Ijma’ can be integrated into modern state legal systems through state institutions such as the Senior Scholars Council in Saudi Arabia, the Guardian Council in Iran, the Council of Islamic Ideology in Pakistan, or substantively through the moral and social influence of religious institutions such as the Indonesian Ulama Council (MUI). Ijma’ can function as a consultative and collective legislative mechanism that strengthens the legitimacy of national law, provided that the process adheres to the principles of scholarly authority, open consultation, and a focus on the public interest (maslahah ‘ammah). With a systemic, inclusive, and contextual approach, ijma’ can be transformed into an instrument of legal reform that is responsive to the needs of modern society, while maintaining the continuity of Islamic legal tradition as an ethical and epistemological pillar in the formation of state law.